OVERHEAD PROJEKTOR AND IT´S USAGE IN LESSONS - RŮŽIČKA, Evžen (Trends in education, 2008)
In todyas world is the computer vone of the most progressive didactic medium. We can use computer in many wals in education. We can komplete computer with added apparates, mostly with overhead projektor. This arrangement is good didactic medium, which help us to produce new type sof lessons. Overhead projektor is very flexible. To use it and manipulate with it is easy. At schools there are some probléme with it´s usaje, so we lay out some didactic notes for help. It can help to everyone, not just only to teachers.
Keywords: Education; didactic medium; overhead projektor; computer; didactic theses.